Pediatric and Adult Ambulatory Blood Pressure Thresholds and Blood Pressure Load as Predictors of Left Ventricular Hypertrophy in Adolescents. Issue 1 (10th May 2021) - Hamdani, Gilad; Mitsnefes, Mark M.; Flynn, Joseph T.; Becker, Richard C.; Daniels, Stephen; Falkner, Bonita E.; Ferguson, Michael; Hooper, Stephen R.; Hanevold, Coral D.; Ingelfinger, Julie R.; Lande, Marc; Martin, Lisa J.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Ambulatory blood pressure (BP) monitoring is the accepted standard to confirm the diagnosis of hypertension. Although adult guidelines use absolute BP cut points to define ambulatory hypertension, current pediatric guidelines define it based on sex- and height-specific 95th percentiles and BP loads. To examine the association of different ambulatory BP parameters with hypertensive target organ injury, we compared adult and pediatric cut points and assessed the utility of BP load as a predictor of left ventricular hypertrophy (LVH) in 327 adolescents who were ≥13 years of age. Logistic regression was used to assess association of different ambulatory BP parameters with LVH. Sensitivity and specificity of different ambulatory BP cut points as predictors of LVH were also calculated. Sixty-eight (20.8%) participants had LVH. In the analysis comparing adult and pediatric criteria for ambulatory hypertension to predict LVH, adult cut points had better sensitivity-specificity balances than the pediatric 95th percentiles. Although the adult cut point for sleep systolic BP (110 mm Hg) was the optimal predictor of LVH, lower cut points for wake systolic BP (125 mm Hg) and 24-hour systolic BP (120 mm Hg) were better predictors of LVH than adult cut points. In a separate analysis, mean systolic BP, but not BP load, was significantly associated with LVH. We conclude that a single static cut point using an absolute ambulatory systolic BP value is comparable to sex-and height-based systolic BP percentiles in predicting LVH and that BP load does not provide any additional (to mean systolic BP) value to predict LVH in adolescents.